Ion exchange in photoactivated inorganic matters - Dikiy, N.P.; Dovbnya, A.N.; Lyashko, Yu.V.; Medvedev, D.V.; Medvedeva, E.P.; Parhomenko, Yu.G.; Uvarov, V.L.; Fedorets, I.D. (Вопросы атомной науки и техники, 2017)
The effects of monovalent and bivalent impurities on the diffusive mobility sodium, caesium and strontium in magnesium potassium phosphate hexahydrate and clinoptilolite were analysed. It was determined that ratio of diffusion coeffcients of sodium concerning caesium and strontium are in antagonistic dependence on the caesium and strontium content in a matrices on the basis of magnesium potassium phosphate hexahydrate. It is established that the diffusion process in the magnesium potassium phosphate hexahydrate is due to the Frenkel. The influence of the diffusion of impurity elements as a function of the ionic radius and the ion position in the crystal lattice of clinoptilolite has been studied. Проаналізовано вплив моновалентних і двовалентних домішок на дифузійну рухливість натрію, цезію і стронцію в гексагідраті фосфату калію магнію. Визначено, що відношення коефіцієнтів дифузії натрію щодо цезію і стронцію знаходяться в антагоністичній залежності від вмісту цезію і стронцію в матрицях на основі гексагідраті фосфату калію магнію. Встановлено, що дифузійний процес у гексагідраті фосфату калію магнію обумовлений механізмом Френкеля. Вивчено вплив дифузії домішкових елементів в залежності від іонного радіуса і займаної позиції в кристалічній решітці кліноптілоліта. Проанализировано влияние моновалентных и двухвалентных примесей на диффузионную подвижность натрия, цезия и стронция в гексагидрате фосфата калия магния. Определено, что отношения коэффициентов диффузии натрия относительно цезия и стронция находятся в антагонистической зависимости от содержания цезия и стронция в матрицах на основе гексагидрата фосфата калия магния. Установлено, что диффузионный процесс в гексагидрате фосфата магния обусловлен механизмом Френкеля. Изучено влияние диффузии примесных элементов в зависимости от ионного радиуса и занимаемой позиции в кристаллической решетке клиноптилолита.